Materiales de la zona como recursos para resolver problemas aditivos - Ramirez Alata, Maribel (2021)
The purpose of this research work is to work on problem solving supported with available resources in the area, with students of the third grade of primary education of the Educational Institution Nº 0736 of the village of Pushurumbo district and province of Tocacche, San Martin region. Likewise, problem solving is based on the polya theory, which proposes four steps to solve mathematical problems and one of them consists of the student reading the problem calmly, thus achieving his understanding and when he already understood the situation and the goal. to which you want to reach, begins to explore which way you can follow to solve the problem, Therefore, the action plan in my research work I have considered convenient to use resources from the area such as: seeds, seeds of various plants and in different sizes and shapes to be able to exchange units, tens, hundreds and simulations of the problems posed that have arisen as part of everyday life, which will allow us to improve their understanding and learning in solving significant problems: Therefore, the use of resources is based on Piaget, who tells us about teaching materials that stimulate the function of the senses to access a an easy way to acquire skills and abilities of students by solving problems in a systematic, logical and methodical way, that is why the methodology I have used is for students to collect different seeds and place them in their bags pretending that they are their products such as coffee, cocoa, beans, canes and other fruits and they place it in the little store, this strategy used has allowed the students to begin to reflect, to be more skillful, to handle mathematical problem solving in an abstract way, to add, subtract at the time of do your shopping.